Prevalence of IgM and IgG antibodies to Toxoplasma gondii in blood donors in the Czech Republic - Svobodová, V; Literák, I (European journal of epidemiology, 1998)
Blood donors (n = 663) from the Nový Jicín district, Czech Republic, were examined for the presence of antibodies to Toxoplasma gondii. The indirect fluorescent antibody test was used to simultaneously detect IgM and IgG antibodies. Titres > or =20 were considered positive. The seroprevalence of IgM and IgG antibodies was 2.4% and 32.1%, respectively. Periods, for how long the blood donors were infected, are discussed.
Keywords: Humans; toxoplazmóza; lidé středního věku; imunoglobulin G; rozložení podle pohlaví; fluorescein-5-isothiokyanát; Female; Toxoplasmosis; dospělí; séroepidemiologické studie; lidé; zvířata; Blood Donors; věkové rozložení; Adult; fluorescenční protilátková technika nepřímá; fluorescenční barviva; ženské pohlaví; Fluorescent Dyes; Toxoplasma; Male; Middle Aged; Seroepidemiologic Studies; Adolescent; protilátky protozoální; Czech Republic; Age Distribution; Fluorescein-5-isothiocyanate; Sex Distribution; Antibodies, Protozoan; dárci krve; imunoglobulin M; Animals; Fluorescent Antibody Technique, Indirect; Česká republika; mužské pohlaví; Immunoglobulin G; Immunoglobulin M; mladiství